Game Theory: Conflict and Cooperation - Venslauskaitė, Goda Izabelė (Problemos, 2000)
The article gives an overview of the basic concepts of Game Theory, such as zero sum game and non-zero sum game for two players, von Neumann’s mini-max theorem, Pareto optimum, simple and iterated Prisoner’s dilemma, Evolutionary stable strategy. Game Theory is understood as an analytical tool dealing with situations of conflict and co-operation. One of the main ideas of the theory is that by reducing and simplifying complicated phenomena of our everyday world we can often find a simple game situation with a single or more solutions. The theory helps to search for solutions by constructing ideal types of situations that contain principal elements of rational choice. There is no claim that Game Theory is something completed and not problematic itself and yet it provides elegant logical tools for analysis of social, political and philosophical life.